Segredos ìntimos: a gestão nos assentamentos de reforma agrária - Alencar, Francisco Amaro Gomes de (1998)
Intimate secrets – the management of agrarian reform settlements” is result of my reflections and experience working during the last twelve years as geographer, firstly as a technician and lately as an university professor. This knowledge was built along with the settiers, using an approach that searches to bring to the theory mechanisms that involve the construction of knowledge in this field. This is a rigorous, systematic, and critic research. Its content is justified through the successive approximations of the studied subject: settler / settlement due to the way that the reality was historically formulated. The results are neither conclusive nor definitive because “durable works are not finished yet”. Therefore, I begin analyzing the undertanding of the categories: settlement in agrarian reform areas, management, place, space, and territory. In following, I (re)interpret the history of the studied subject, having as case study the settlements Vitória and Cachoeira Cercada, in order to demonstrate from this standpoint the relationship between a successful settlement and another one that did not achieve “success”. Finally, I propose a way to be followed so that the settlers succeed in managing the territory, instead of keeping managing the space or the place “forever”.